2007
DOI: 10.1590/s1413-78522007000100008
|View full text |Cite
|
Sign up to set email alerts
|

Retalho cutâneo das artérias perfurantes do músculo gastrocnêmio medial: estudo anatômico

Abstract: OBJETIVO: Estudo dos parâmetros anatômicos da irrigação do retalho cutâneo baseado nas artérias perfurantes do músculo gastrocnêmio medial através da artéria sural medial. MATERIAL E MÉTODOS: dissecção de doze pernas e análise dos parâmetros como comprimento e largura do músculo gastrocnêmio medial, quantidade de vasos perfurantes para o retalho cutâneo, comprimento e largura do pedículo da artéria sural medial e origem da artéria sural medial em relação ao cavo poplíteo, além de dados localizatórios das perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…The results of our anatomic study were similar to studies by Torres et al and Otani et al which place the distal most medial and lateral gastrocnemius muscle perforators at 16.3 and 17.5 cm distal to the popliteal crease or the intercondylar line. 11,12 Regarding the number of perforators arising from the lateral head our results were different from the study by Otani et al which did not find any cutaneous perforator in 57% of the cases while we found at least 1 cutaneous perforator from the lateral head in 100% of the cadaveric dissections…”
Section: Discussioncontrasting
confidence: 99%
“…The results of our anatomic study were similar to studies by Torres et al and Otani et al which place the distal most medial and lateral gastrocnemius muscle perforators at 16.3 and 17.5 cm distal to the popliteal crease or the intercondylar line. 11,12 Regarding the number of perforators arising from the lateral head our results were different from the study by Otani et al which did not find any cutaneous perforator in 57% of the cases while we found at least 1 cutaneous perforator from the lateral head in 100% of the cadaveric dissections…”
Section: Discussioncontrasting
confidence: 99%
“…The gastrocnemius and soleus muscles, being vascularized predominantly in their proximal regions, allow the rotation about the axis of the pedicle (good arc of rotation), without compromising vitality. They thus offer a good option for bone and soft tissue coverage of the Table 1 Table 1 Table 1 Table 1 Table 1 proximal and middle thirds of the leg, being the most used, usually individually [8][9][10][11][12][13][14][15][16] . In some situations, one may employ the soleus associated with one of the belies of the gastrocnemius 17 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…34 In the subsequent clinical experience, increasingly larger skin islands were lifted from the flap without presenting damage. Accordingly, the muscle becomes, for the most distant defects, a "carrier" of vascularized skin.…”
Section: Methodsmentioning
confidence: 99%